Omnichannel Customer Experience Model towards Customer Repurchase Intentions and Word of Mouth on Cellular Products Loyalty - Teuku Dhani Al Ramdhani; Ratih Hurriyati; Heny Hendrayati; Mokh Adib Sultan (STMIK Dharma Wacana, 2025)
Customer loyalty to mobile products in Indonesia is influenced by various factors, including download speed, upload internet speed, latency, streaming, and browsing. This study aims to analyze the effect of Omnichannel Customer Experience (OCX) on Cellular Product Loyalty (CPL) through the mediation role of Customer Repurchase Intentions (CRI) and Word of Mouth (WoM). This study uses an explanatory survey design involving 384 mobile product users throughout Indonesia, who were selected using proportional sampling techniques. Data analysis was carried out using descriptive and verification methods, using Structural Equation Modeling - Partial Least Square (SEM-PLS) to test the relationship between variables. The findings of the study indicate that OCX does not have a direct effect on CPL, but must go through the mediation of CRI and WoM. Between the two mediators, WoM has a stronger influence than CRI, indicating that a positive omnichannel experience encourages customers to recommend products, ultimately increasing customer loyalty. The novelty of this research lies in simultaneously testing the relationship between OCX, CRI, and WoM on CPL in the context of the cellular industry, as well as identifying the more dominant mediation pathways in increasing customer loyalty. The implications of this research provide insights for telecommunications companies to focus more on omnichannel strategies that can improve customer experience and encourage Word of Mouth, as well as for the government in designing policies that support the digital ecosystem for the cellular industry in Indonesia.